Effects of Phenolics on the Physicochemical and Structural Properties of Collagen Hydrogel - Munir, Sadia; Yue, Wei; Li, Jinling; Yu, Xiaoyue; Ying, Tianhao; Liu, Ru; You, Juan; Xiong, Shanbai; Hu, Yang (Polymers, 2023)
In the current era, the treatment of collagen hydrogels with natural phenolics for the improvement in physicochemical properties has been the subject of considerable attention. The present research aimed to fabricate collagen hydrogels cross-linked with gallic acid (GA) and ellagic acid (EA) at different concentrations depending on the collagen dry weight. The structural, enzymatic, thermal, morphological, and physical properties of the native collagen hydrogels were compared with those of the GA/EA cross-linked hydrogels. XRD and FTIR spectroscopic analyses confirmed the structural stability and reliability of the collagen after treatment with either GA or EA. The cross-linking also significantly contributed to the improvement in the storage modulus, of 435 Pa for 100% GA cross-linked hydrogels. The thermal stability was improved, as the highest residual weight of 43.8% was obtained for the hydrogels cross-linked with 50% GA in comparison with all the other hydrogels. The hydrogels immersed in 30%, 50%, and 100% concentrations of GA also showed improved swelling behavior and porosity, and the highest resistance to type 1 collagenase (76.56%), was obtained for 50% GA cross-linked collagen hydrogels. Moreover, GA 100% and EA 100% obtained the highest denaturation temperatures (Td) of 74.96 °C and 75.78 °C, respectively. In addition, SEM analysis was also carried out to check the surface morphology of the pristine collagen hydrogels and the cross-linked collagen hydrogels. The result showed that the hydrogels cross-linked with GA/EA were denser and more compact. However, the improved physicochemical properties were probably due to the formation of hydrogen bonds between the phenolic hydroxyl groups of GA and EA and the nitrogen atoms of the collagen backbone. The presence of inter- and intramolecular cross-links between collagen and GA or EA components and an increased density of intermolecular bonds suggest potential hydrogen bonding or hydrophobic interactions. Overall, the present study paves the way for further investigations in the field by providing valuable insights into the GA/EA interaction with collagen molecules.